«How they had beaten him!»: the disappearance of childhood in César Vallejo’s short stories - Carhuaricra Anco, Miguel Ángel (2023)
César Vallejo’s latest narratives are sources for tracing his perspective on school and childhood, topics that have been interpreted from a sociological, political and cultural orientation. This article analyses and interprets the significance of childhood in Vallejo’s stories from the premises of tensional semiotics. The idea that guides this study is that, in the stories «Paco Yunque» and «El vencedor», the corporeality of the actors configures and warns of the disappearance of childhood. For this purpose, we will first present the trajectory of César Vallejo’s narrative and the critical views on his stories belonging to the period 1931- 1936; then we will explain the dimensions of the actant-body from the semiotic guidelines of Jacques Fontanille; subsequently, we will analyse and interpret the significance of the body in the stories mentioned; and, finally, we will reflect on the importance of knowing the complex affectivity of childhood and its implications in the educational scenario.